Monitoramento de Aedes aegypti (Linnaeus, 1762) e de características sócio ambientais na construção de estratégias de controle da dengue, em Cuiabá, MT - Cruz, Lucinéia Claudia De Toni Aquino da (2013)
The measures for dengue control basically concentrate on Aedes aegypti's vector elimination, however other aspects must be investigated permanently. In this paper, the goal was to analyse the contribution of Aedes aegypti's monitoring of socio-environmental characteristics for strategies of dengue control, in an area of Cuiabá-MT, in 2012. The area was chosen for signalling a high risk of dengue transmission. Ovipositions traps were used, called ovitraps, in 10 randomly chosen points. Data collection period occurred in three cycles of 2012. 2728 eggs were collected, observing the Eggs Density Index (IDO in Portuguese) and Ovitraps Positivity Index (IPO in Portuguese). Climatic variables signalized a correlation to the number of eggs in precipitation and humidity. In environment's physical analysis, the predominating breedings were the removable kind. The reason of prevalecence was calculated to analyse the ovitraps' microenvironment, being found variables with risk factors for the increase of eggs' number. The visits of the Endemies Control Agent (ACE, in Portuguese), in residences corresponding to the same period of study were also observed. In some estates the interval between visits was up to 38 days, which did not influence on the increase of eggs' number. The second part of the research aimed to estimate the transovarian Minimum Infection Rate (TMI in Portuguese) in a sample of insects hatched from ovitraps. A total of 758 were stores in -80ºC for RNA extraction through RT PCR by trizol method. Eight positive pools were found out of 50 tested, with a 10,55% TMI. The four sorotypes of dengue, YFW (Yellow Fever), WNV (West Nile) and SLEV (SaintLouis) were analysed, however only sorotype 4 from DENV was detected in the samples. In conclusion, it was possible to demonstrate that the ovitrap is a sensible, efficient method. Analysed with physical and climatic conditions, they contributed for a bigger vectorial comprehension of the area. Through viral analysis, it was testified that transovarian transmission is happening in the region, and its epidemiological importance still needs to be better assessed, in bigger samples and more diverse areas.